Hybrid Palliation for a Neonate With Functional Single Ventricle and Restrictive Atrial Septal Defect: A Case Report. (January 2015) - Sasaki, Takashi; Asou, Toshihide; Takeda, Yuko; Tominaga, Takashi; Onakatomi, Yasuko; Ueda, Hideaki; Kawataki, Motoyoshi
We present the case of a neonate who was successfully treated with emergency hybrid palliation soon after birth, including a stent insertion into a severely thickened atrial septum and bilateral pulmonary artery banding. The patient was prenatally diagnosed with severe pulmonary venous hypertension owing to mitral atresia and intact atrial septum associated with functional single ventricle and coarctation of the aorta.